Effectiveness of school-based physical activity programs in enhancing attention, academic performance, and social relationships among children with intellectual disabilities: evidence from Pakistani schools - Sabri, Saima; Zhang, Mei-Yue; Guo, Lu; Dang, Junhua; Mao, Zhi-Xiong (Frontiers in Psychology, 2024)
Physical activity (PA) offers extensive benefits for all children, including those with intellectual disabilities (ID), who face significant challenges in behavioral management and psycho-social well-being. This study investigates the effects of school-based PA on attention, academic performance, and relationships with teachers and parents in children with ID. A 12week single-blind randomized controlled trial was conducted with 102 children with ID, aged 6 to 12 years (71 boys and 31 girls) from grades 1 to 5. Participants were divided into three groups: MVPA (moderate to vigorous PA), MPA (mild PA), and NPA (no PA). Each group engaged in PA three times a week for 45 minutes per session, with activities planned by a fitness trainer and supervised by the researcher. Outcome measures were assessed using SNAP-IV, STRS, CPRS, and APRS scales before and after the intervention. The results indicated that MVPA had a more significant positive impact on all outcomes compared to MPA and NPA. MPA also produced notable improvements relative to NPA. These findings underscore the importance of integrating PA into educational settings as a comprehensive strategy to enhance attention, academic performance, and social interactions for children with ID. This research highlights PA as a vital tool for addressing behavioral challenges and fostering better developmental outcomes in this population.